Innovative Approaches to the Use of Information Technologies in the Process of Teaching Mathematics (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
Among the means of teaching mathematics, information technology has occupied its important place for a long time. The use of multimedia presentations, test shells, electronic textbooks, specialized programs for graphing functions or geometric objects has become an integral part of the process of teaching mathematics. The constant development of information technology offers other options for their use in the educational process, discussed in this article. The use of interactive exercises, mobile devices, interactive whiteboards, services for creating mental maps, microblogging, applications based on augmented reality allows implementing innovative approaches to the process of math teaching. This article analyzes the applications that allow these opportunities to be implemented, the directions of their application in the educational process are considered, and guidelines for their use in the process of teaching mathematics are given in order to increase the cognitive activity and interest of students, as well as the effectiveness of the learning process as a whole.